A novel antioxidant sulfated polysaccharide from the algae Gracilaria caudata: In vitro and in vivo activities. (May 2019) - Alencar, Poliana O. Cavalcante; Lima, Glauber C.; Barros, Francisco Clark N.; Costa, Luís E.C.; Ribeiro, Carla Vivianne P.E.; Sousa, Willer M.; Sombra, Venícios G.; Abreu, Clara Myrla W.S.; Abreu, Ewerton S.; Pontes, Edivânia O.B.; Oliveira, Ariclécio C.; de Paula, Regina C.M.; et al.
Abstract: Marine red macroalgae are natural sources of sulfated polysaccharides, water-binding molecules used in the food industry as thickeners, stabilizers and gelling agents. Sulfated polysaccharides extracted from the red seaweed Gracilaria caudata also show biological activities with potential therapeutic effects against diseases associated with oxidative stress; hence, it is possible that they may be used as nutraceuticals and/or food additives. This study aimed to obtain the sulfated polysaccharides from G. caudata (SP-Gc) through enzymatic extraction and to determine their chemical structure and antioxidant potential. Inductively Coupled Plasma-Optical Emission Spectrometry showed that SP-Gc have 0.9% of sulfur atoms and a degree of sulfation of 0.14%. An average molecular mass of 116.51 kDa was determined through gel permeation chromatography. The SP-Gc structure as an agar-type galactan was determined by Fourier transform infrared (FTIR) spectroscopy and nuclear magnetic resonance (NMR) spectroscopy ( 13 C and 1 H). The in vitro antioxidant activity of SP-Gc was determined through the following tests: ferrous ion chelating ability and total antioxidant capacity. The results indicated that SP-Gc have significant antioxidant activity in a concentration-dependent manner. The in vivo antioxidant activity of SP-Gc was evaluated in an oxidative stress model induced by 2, 2′-azobis(2-methylpropionamidine) dihydrochloride (ABAP) in rats pretreated with SP-Gc (3 and 10 mg/kg). Catalase (CAT) and superoxide dismutase (SOD) levels were measured and all doses increased CAT and SOD activity. These results demonstrate that SP-Gc may be used as hydrocolloids, due to their characterization as agar, and as nutraceuticals, due to their antioxidant activity. Graphical abstract: Image 1006 Highlights: Sulfated polysaccharides from G. caudata (SP-Gc) are agar-type galactans. SP-Gc exhibited significant antioxidant in vitro activity. Results equally satisfactory were achieved when compared to synthetic antioxidants. SP-Gc exhibited significant antioxidant in vivo activity after ABAP-induction. SP-Gc may be used as hydrocolloids and as nutraceuticals in the food industry.